Answer:
I can't see the questions please make bigger
Step-by-step explanation:
Answer:
C
Step-by-step explanation:
An equation is where you already have the answer but you have to find out what the variable is to prove that the equation is true.
Answer:
1598.2
Step-by-step explanation:
I used a calculator on this one.
Answer:
x = 2
4 (x + 6) - 3x = 26
solve the parenthesis
4x + 24 - 3x = 26
subtract 24 from both sides to get x by itself
4x - 3x = 2
solve
x = 2
Should be 8)/3 = (3x - 8 + 8)/3 = 3x /3 = x.